The importance of physiologic mechanisms in the treatment of diabetic macular edema - (:unkn) unknown (My University, 2011)
Diyabetik maküla ödeminde tedavi seçenekleri fazladır. Bu yüzden diyabetik maküla ödemi tedavi seçenekleri arasında doğru kombinasyona karar verirken altta yatan fizyolojik mekanizmaları anlamak önemlidir. Burada altta yatan fizyolojik mekanizmaları göz önünde bulundurarak diyabetik maküla ödeminin tedavi seçeneklerini kısaca gözden geçirdik.

There are multiple different treatment options of diabetic macular edema. Therefore it is important to understand the physiological mechanism of these treatment modalities when deciding the appropriate combination of treatment options. We herein present a brief review of available treatment options of diabetic macular edema with particular consideration of the mechanisms of action.
Diyabetik maküla ödemi tedavisinde fizyolojik mekanizmaların önemi
Keywords: Genel ve Dahili Tıp